Nest-specific composition of the trail pheromone of the stingless bee Trigona corvina within populations - John, Lena (2012)
Social insects have evolved highly developed communication systems, enabling them to coordinate complex interactions in their colonies. Pheromones play a major role in the coordination of many tasks. In Trigona corvina, a stingless bee that occurs in Central America, foragers use pheromones produced in their labial glands to scent mark solid substrates between a food source and their nest. Newly recruited bees subsequently follow these scent marks until they reach the food source. A recent study has revealed nestspecific differences in the composition of these trail pheromones in colonies of T. corvina, suggesting that pheromone specificity may serve to avoid competition between foragers from different nests. However, the nests used in this study came from different populations and their foragers certainly never met in the field (Jarau et al., 2010). The aim of the present study was to investigate whether differences in the trail pheromones of foragers from different nests can also be found between neighbouring colonies within populations. We analysed the composition of trail pheromones from labial gland secretions extracted from workers from nine colonies collected at three different populations in Costa Rica. The differences in pheromone composition were even more distinct between neighbouring nests within a population than between nests of different populations. This finding corroborates the hypothesis that nest specificity of trail pheromones serves to communicate the location of a food source exclusively to nestmates, thereby avoiding intraspecific competition at resources. Resource partitioning by avoiding conspecific non-nestmates is particularly adaptive for aggressive bee species, such as T. corvina.